The Implications of a Supreme Law Bill Of Rights for New Zealand Judicial Appointments - Bull, Juliet (Victoria University of Wellington Law Review, 2015)
The enactment of a supreme law Bill of Rights in New Zealand would have significant implications for the process of appointing judges. This article considers whether the present judicial appointments system should be retained were New Zealand to amend the New Zealand Bill of Rights Act 1990 to have supreme law status. It contends that the present appointments process is insufficiently transparent and offers too few checks and balances to safeguard the apolitical nature of appointments. Canada’s experience after enacting the Canadian Charter of Rights and Freedoms is drawn upon to demonstrate the need for reform. After various options are considered, it is ultimately contended that the adoption of a supreme law Bill of Rights in New Zealand should be accompanied by the creation of a judicial appointments commission.